TEACHER PROFESSIONAL DEVELOPMENT AT MIN 2 BANTUL FOR THE IMPLEMENTATION OF TECHNOLOGY-BASED LEARNING - Akifatun Nafisah; Sularso (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the professional development of teachers at MIN 2 Bantul in the implementation of technology-based learning. With the advancement of technology, technology-based learning has become crucial in improving the quality of education. This study uses a qualitative approach with a case study method at MIN 2 Bantul. Data was collected through interviews, observations, and documentation. The results indicate that the professional development of teachers through technology training, both online and face-to-face, can enhance teachers' understanding of implementing technology in teaching. Despite challenges, such as limited infrastructure and teacher readiness, continuous development of competencies is being conducted to achieve more effective learning. The implementation of technology in the classroom also positively impacts student interaction and motivation to learn. The study concludes that continuous professional development of teachers is key to the successful implementation of technology-based learning in schools.